A Implementasi Pasal 214 Undang-Undang Nomor 23 Tahun 2014 Tentang Pemerintahan Daerah Dalam Penunjukan Penjabat Sekretaris Daerah Provinsi Maluku: IMPLEMENTATION OF ARTICLE 214 OF LAW NUMBER 23 OF 2014 R CONCERNING REGIONAL GOVERNMENT IN THE APPOINTMENT OF THE ACTING REGIONAL SECRETARY OF THE MOLLUCAS PROVINCE - Martha Riananda; Malicia Evendia; Steven Edoward Salasiwa (Legalita, 2022)
Abstract: The acting Regional Secretary of the Moluccas Province is an official appointed to occupy the position of Regional Secretary which is temporary, because the Regional Secretary is still (definitively) unable to carry out his duties so that there is a “vacancy” of the Regional Secretary. Then some media circles think that there is an element of politicization in the appointment of the Acting Secretary. Moluccas Province Regional. However, it was different during an interview with Karsul Selang, S.T., M.T. According to him, the appointment of the acting Regional Secretary by the Governor of Moluccas Province to Sadli Le, S.Hut., M.Si. is the authority of the Governor as referred to in Article 214 of 2014 Law Number 23 of 2014 concerning Regional Government, the appointment is normative because Sadli Le, S.Hut., M.Si. has received a recommendation from the Minister of Home Affairs and the appointment of the Governor of Moluccas Province as the representative of the central government.